The influence of functional states on the normative indicators of cross-country running of students before and after the COVID-19 pandemic - I.P. Zaitseva (Theory and Practice of Physical Culture, 2023)
Objective of the study was to assess the impact of functional states on the performance of normative indicators of cross-country running of students before and after the COVID-19 pandemic. Methods and structure of the study. 42 subjects took part in the scientific work (gender - female, average age 19.5 years, health group - main). Group X - students who took the Applied Physical Education course in full-time before the start of the pandemic (duration of the course: 2015-2018); group Y - students who took the course "Applied Physical Education" in full-time and remote form during the pandemic (duration of the course: 2019-2022). To measure the level of fatigue, monotony, satiety and stress, the method "Differential diagnosis of conditions of reduced performance" (DORS) by A.B. Leonova and S.B. Velichkovskaya (modified). A comparative evaluation of the results of a 3000 m cross-country run was also carried out. Results and conclusions. The conditions of self-isolation, distance learning and quarantine measures during the pandemic had an impact on the physical and mental health of students who had an increased level of monotony, a lower result in cross-country running than in the group of students involved in the traditional mode of study before the pandemic. The results obtained give grounds to assume that the limitation of life activity leads to dysfunction of the motivational-volitional sphere, apathy, boredom, physical and mental fatigue of students and, accordingly, affects their results in long-distance running. The issue of maintaining health, both physical and psychological, in conditions of self-isolation is still relevant, and therefore there is an increasing need to develop and apply various types of monitoring the results of people’s motor activity in various conditions of life.